Teaching Religion OR about Religion: The Paradox of Religious Education in Secondary Schools in Uganda - Bweyale, Josephine; Tugume, Lubowa Hassan (East African Journal of Traditions, Culture and Religion, 2021)
The article reviews the teaching of Religious Education in schools in Uganda. Uganda is a religiously pluralistic country with Christianity and Islam the most popular. Ugandans are theists, their worldview is religious and they are passionate about their faiths. Therefore, Religious Education is a fundamental subject since the early years of education as it marked the beginning of formal education in Uganda. However, whilst Uganda has a diversity of religions such as Christianity with its different sects, Islam and its sects, Hinduism, Buddhism, and Sikhism, the education system considers only Islam and Christianity. Therefore, the article discusses whether the teaching of Religious Education where only Christianity and Islam are considered is justified to be referred to as Religious Education. The article concludes that there is a mismatch between the NCDC (2008) stated goals, objectives and content of Religious Education. The objectives and goals portray a false image that RE is intended to expose learners and to achieve educational purposes. Yet, the content, approaches and teaching methods are quite contradictory. The implementation of RE in Uganda is purely confessional; it does not aim at educational goals but at deepening learners' faith distinctively. Instead of teaching about religion, learners are taught religion. The article is based on documentary analysis of the Religious Education curriculum, syllabi and teachers' and learners' handbook documents. In addition, the article analysed literature about the teaching of Religious Education including the aims and goals of Religious Education, the pedagogical approaches, methods and techniques in Religious Education in modern pluralistic communities. In identifying the appropriate literature, suitable databases were identified and used Boolean operators and proper search terms, phrases and conjunctions were used. To further ensure the credibility of the reviewed publications for analysis, only peer-reviewed journal articles with ISBN numbers and Digital Object Identifiers (DOI) were used